A relação da inteligência emocional com os traços patológicos de personalidade - Nagae, William Hiody Schmidt (Universidade Federal de São Carlos, 2021)
The Emotional Intelligence (EI) is defined as the ability of perceiving, using, understanding and managing emotions. It has been studied by several researchers for more than 30 years. For a further insight into EI and how it relates to other constructs, one of the research lines is dedicated to Personality. Although the studies are recurrent with personality traits, there is a lack of correlations with personality disorders. Thus, the objective of the current study is to investigate the relationship between the EI and the pathological personality traits. In this study. 101 adults of both sexes participated of this research and answered two online questionnaires that measure EI. Both are part of the Bateria de Inteligência Emocional. One of them is related to emotional perception and the other one is related to emotional regulation. The Inventário Dimensional Clínico da Personalidade – II was also used to check pathological personality traits. The results obtained revealed that the large majority of them are in agreement with literature, that also indicates the presence of significant, weak and negative correlations between pathological traits and EI. This research also endorses the previous hypothesis of the literature about the existence of a bivalent influence between the EI, pathological traits and personality disorders. In conclusion, as a result of the gap of previous studies, more researches are expected to continue studying about that relationship, and it is expected that this study contributes to future discussions.
The relationship between emotional intelligence with pathological personality traits
Keywords: Emotional intelligence; Inteligência emocional; Personality disorders; Transtorno da personalidade; Avaliação da personalidade; Personality assessment; CIENCIAS HUMANAS::PSICOLOGIA